2014
DOI: 10.1097/scs.0000000000000556
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Mechanical Thermal Analysis of Maxillofacial Prosthetic Elastomers

Abstract: In this study, dynamic mechanical thermal analysis was used to evaluate the changes that occurred in maxillofacial elastomers subjected to different disinfecting regimens. A commercial polydimethyl siloxane (PDMS) and an experimental chlorinated polyethylene (CPE) were treated with different disinfection procedures for a period that simulates 1 year of clinical service: microwave exposure (D1), hypochlorite solution (D2), neutral soap (D3), and a commercial disinfecting solution (D4). A fifth group was kept in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 40 publications
1
11
0
1
Order By: Relevance
“…The activity of the mitochondrial dehydrogenase reduces the XTT tetrazolium salt to formazan salt, resulting in a colorimetric change correlating with the cell viability. 29 An XTT salt solution (Sigma-Aldrich) was prepared in ultrapure water at a final concentration of 1 mg/mL, and menadione solution (0.4 mM in acetone; Sigma-Aldrich) was prepared immediately before each assay. The disinfection solutions were added to each well of a microtiter plate containing 1 silicone specimen to be tested for 10 minutes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The activity of the mitochondrial dehydrogenase reduces the XTT tetrazolium salt to formazan salt, resulting in a colorimetric change correlating with the cell viability. 29 An XTT salt solution (Sigma-Aldrich) was prepared in ultrapure water at a final concentration of 1 mg/mL, and menadione solution (0.4 mM in acetone; Sigma-Aldrich) was prepared immediately before each assay. The disinfection solutions were added to each well of a microtiter plate containing 1 silicone specimen to be tested for 10 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…17,19,20 Chemical disinfection using nonirritating disinfectant solutions ensures the health of tissues that come into contact with prostheses because, when properly cleaned, the risk of infection is minimized. [13][14][15][16] Conventional cleaning protocols involve mechanical biofilm removal (with manual toothbrushing or washing by hand with water and neutral soap), [21][22][23][24][25] effervescent solutions such as cleansing tablets, [22][23][24][25] sodium hypochlorite 0.5% to 1%, [26][27][28][29] and chlorhexidine 2% to 4%. 13,[22][23][24][30][31][32][33] However, frequent exposure to these solutions may interfere with the properties of silicone.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 Also, some investigations suggest that digital friction induces the detachment of the additives that are incorporated into the elastomer matrix, even when it is performed gently; unfortunately, hygiene procedures for facial prostheses are mandatory, so this cannot be avoided. [18][19][20] This factor might also explain the excessive number of small repairs (retouches) that were observed in nearly all patients. Figure 1 shows that most of the prostheses failed 1 to 3 years after clinical installation, indicating that the mean life span of the prostheses is similar to the values previously reported by other clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…1,[13][14][15][16] However, the most common reason for the replacement of facial prostheses is the impairment of the properties of silicone elastomers, which is generally identified by the discoloration or failure of the material. 6,[13][14][15][16][17][18][19][20][21][22] This deterioration is caused primarily by exposure to weather conditions, human body secretions, and prosthesis maintenance procedures. 1,6,12,23 Some studies have reported that the mean life span of a silicone-based facial prosthesis ranges from between 1.5 and 3 years, with only a small percentage of prostheses (4.8%) lasting longer than 2 years.…”
mentioning
confidence: 99%